2019
DOI: 10.1371/journal.pone.0219958
|View full text |Cite
|
Sign up to set email alerts
|

Species composition, diversity, and distribution of the genus Ulva along the coast of Jeju Island, Korea based on molecular phylogenetic analysis

Abstract: Species diversity in the genus Ulva remains understudied worldwide. Using molecular analyses we investigated the species composition, diversity, distribution, and relative frequencies of the genus Ulva along the entire coast of Jeju Island, off the southern tip of Korea. Species identification was performed for 215 samples collected from 23 sites, based on comprehensive phylogenetic and model-based species delimitation analyses using the sequences of two molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
(85 reference statements)
2
23
0
Order By: Relevance
“…Based on our tufA and rbcL DNA barcoding methods, the presence of with a close phylogenetic relationship to U. laetevirens based on rbcL and internal transcribed spacer (ITS) regions (Matsumoto and Shimada 2015). In addition, this organism was reported from the coast of Jeju Island, Korea (Kang et al 2019). U. pseudo-ohnoi sp.…”
Section: Ulva Laetevirens Areschougmentioning
confidence: 88%
See 4 more Smart Citations
“…Based on our tufA and rbcL DNA barcoding methods, the presence of with a close phylogenetic relationship to U. laetevirens based on rbcL and internal transcribed spacer (ITS) regions (Matsumoto and Shimada 2015). In addition, this organism was reported from the coast of Jeju Island, Korea (Kang et al 2019). U. pseudo-ohnoi sp.…”
Section: Ulva Laetevirens Areschougmentioning
confidence: 88%
“…Historically the identification of Ulva species in Korea has been conducted almost entirely based on morphology, and only a few studies have employed molecular analysis of this genus (Bae and Lee 2001, Kang et al 2014. Kang et al (2019) reported the proportional occurrences of Ulva species using molecular approaches. We determined that the most problematic Ulva bloom, which occurs in Shinyang, is composed of four distromatic and foliose species, U. australis, U. lactuca, U. laetevirens, and U. ohnoi (Table 1), that have attached and free-floating habits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations